Melatonin Treatment of Circadian Rhythm Sleep-Wake Disorder in Obese Children Affects the Brain-Derived Neurotrophic Factor Level - Huang, Xuesong; Huang, Ying; Hu, Bing (Neuropediatrics, 2023)
Background Previous studies proved that the brain-derived neurotrophic factor (BDNF) is correlated with sleep regulation, yet how BDNF functions and reacts in the melatonin treatment of circadian rhythm sleep-wake disorder (CRSWD) among obese children remain enigmatic. Focusing on CRSWD in obese children, this study monitored their sleep efficiency and serum BDNF level changes during the treatment of melatonin.Methods In total, 35 obese children diagnosed with CRSWD were included in this study and administrated melatonin (3 mg/night) for 3 months. Blood samples were collected 24 hours before and after the treatment (08:00, 12:00, 16:00, 20:00, 24:00, and 04:00). Subsequently, the plasma melatonin level and serum BDNF level were measured by enzyme-linked immunosorbent assay. Sleep parameters, including sleep quality, Pittsburgh Sleep Quality Index as well as melatonin and BDNF levels before and after treatment, were recorded to profile the effectiveness and safety of melatonin treatment.Results Melatonin treatment increased plasma melatonin concentration and restored circadian rhythm. Besides, the serum BDNF level showed a significant increase, representing a strong positive correlation with melatonin concentration (p = 0.026). Patients experienced much-improved sleep efficiency (P < 0.001), with longer actual sleep time (P < 0.001), shorter sleep onset latency, and fewer awakenings after treatment (P < 0.001). Besides, melatonin was well tolerated by patients without producing severe side effects.Conclusion Melatonin treatment effectively improved CRSWD among obese children with their serum BDNF levels increased, indicating that BDNF is a key regulator in CRSWD in obese children. This study may offer theoretical support for melatonin treatment of CRSWD in obese children.
Keywords: obese children; circadian rhythm sleep-wake disorder; melatonin; brain-derived neurotrophic factor